1991
DOI: 10.1177/014107689108400305
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: Patients' Expectations in the 1990s

Abstract: A group of 70 patients with inflammatory bowel disease were asked to complete a questionnaire about their disease counselling preferences, 59 replied. Seventy-five per cent wanted further advice about their disease. Of these, 60% wished to receive the advice by discussion with a trained advisor. Seventy-six per cent wanted this person to be a hospital specialist, but 50% would accept advice from a specialty trained nurse. Eighty-six per cent would like this in conjunction with ‘same day’ telephone advice from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Three European studies reported that 70%-80% of participants desired more information about their disease, as they viewed their knowledge to be less than adequate. [15][16][17] There are more recent studies (published since 2000) that present a contrary view of patient knowledge. For instance, only 10% of Irish IBD patients (n ¼ 142) felt that they were poorly informed about their disease and only 15% were very unhappy with their knowledge, while 36% felt they were very well informed and 37% were very happy with their level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three European studies reported that 70%-80% of participants desired more information about their disease, as they viewed their knowledge to be less than adequate. [15][16][17] There are more recent studies (published since 2000) that present a contrary view of patient knowledge. For instance, only 10% of Irish IBD patients (n ¼ 142) felt that they were poorly informed about their disease and only 15% were very unhappy with their knowledge, while 36% felt they were very well informed and 37% were very happy with their level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18]21 This lack of uniformity may reflect varied duration of disease among participants or different methods used to assess information needs. Our study focused on the period shortly after diagnosis, a time when patients are just starting to deal with the challenge of coping with a serious and often chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with in¯ammatory bowel disease voice considerable concern about obtaining all forms of insurance and mortgage. 37 In a study from Leicester in the UK, the attitudes of 50 major insurance companies to patients with in¯ammatory bowel disease, and the experience of a sample of in¯ammatory bowel disease patients were investigated. 38 A standard letter from a`typical' Crohn's disease patient (a 31-year-old male with a disease duration of 6 years, inactive for 5 years after one small bowel resection) was sent out, requesting information about premiums.…”
Section: Life Insurance Issues and Employmentmentioning
confidence: 99%
“…Most notably, within gastroenterology, have been the developments in inflammatory bowel disease (IBD) care. In 1991 Probert et al conducted a questionnaire survey regarding disease counselling preferences in 59 patients with IBD. This landmark paper identified a significant number (60%) who required further information regarding their condition.…”
Section: Introductionmentioning
confidence: 99%